Decoration of Carbon Nanostructures with Metal Sulfides by Sonolysis of Single‐Molecule Precursors. Issue 20 (12th June 2014) - Estrada, Ana C.; Mendoza, Ernest; Trindade, Tito
Abstract: Carbon nanostructures have emerged in recent decades as uniquely convenient materials for a number of technologies. Some of their envisaged applications require hybrid nanostructures that result from the coupling of semiconducting phases to the carbon materials. Here, we describe a new sonochemical method to decorate carbon‐based materials (multiwalled carbon nanotubes, graphene oxide, and graphite flakes) with metal sulfide nanophases. In this research, we have used a Cd II alkyldithiocarbamate complex as a single source to produce CdS nanophases that nucleate and grow over the carbon substrates. However, other metal sulfides can be produced by a similar methodology, which paves the way to a scalable method for the preparation of hybrid metal sulfide/carbon nanomaterials. Abstract : A new method to produce hybrid structures of multiwalled carbon nanotubes (MWCNTs), graphite flakes, or graphene oxide (GO) sheets decorated with metal sulfide (e.g., CdS) nanoparticles is based on the sonolysis of metal alkyldithiocarbamate complexes.